Encyclopedia of marine mammals - Perrin, William F.; Wursig, Bernd G.; Thewissen, J. G. M. (Gale virtual reference library, 2002)
Includes articles devoted to wide range of topics -- from the specific behavior and physiology of cetaceans and pinnipeds, to ecology, population biology, human effects and interaction, and research methodology.